(untitled) (Global Journal of Human-Social Science, 2021)
Silent is a beautiful powerful boost of positive energy and it is an important aspect of worship Our mind is moving towards past and future Bringing mindfulness into the present time during our materialistic society of hectic lives silent evolved as a relief mode for relaxation and happiness World Health Organization and the European Commission s Joint Research Centre concluded that a steady dose of noise pollution could lead to higher blood pressure and fatal heart attacks It was the result of the research found that high rates of cholesterol and hypertension in individuals regularly exposed to loud noises at work In this situation silence can actually stimulate new cell growth in the brain improve memory and release tension in the brain and body In fact two minutes of silence is more effective in relieving physical tension than listening to relaxing music